Determinantes das formas de governança e complementaridades contratuais nas negociações dos produtores de coco do Estado de Alagoas - Gonçalves, Kellyane Pereira dos Anjos (Universidade Federal de São Carlos, 2020)
Brazil is the world's fifth largest producer of coconut. Most of the country’s production is concentrated in the Northeast region. However, since the 1980s, coconut farming has expanded to include almost the entire country, a change motivated by the increase in world consumption of coconut derivatives. In this restructuring process, some traditional states have lost participation nationally. This is the case of Alagoas, which was already the third largest producer in Brazil, prior to the restructuring period. However, in the past few decades, it has persisted in this activity more for social than solely economic aspects – as is tradition of this culture, implanted during the colonial period. In Alagoas, production is practiced, to a greater extent, by family farmers with an area of less than 10 acres. These production systems allow individual farms to unit with other more profitable crop lands. As a result, the low volume of coconut production associated with the coconut tree's seasonality means that most producers' commercialization is restricted to transactions with intermediaries and open markets rather than with cooperatives. Other producers, with greater production volume, trade directly with the few industries installed in that state, in addition to the large intermediaries. In this sense, Alagoas’ restricted marketing channel demonstrates several aspects of organizational evolution through the use of different coordination mechanisms. Thus, the objective of this thesis is to show and analyze the determinants of the adoption of hybrid organizational arrangements and the contractual complementarities in coconut transactions in Alagoas. Studying such transactions is relevant due to the characteristics of their buyers, formed by a few agents, but with different organizational structures. As a result, the bargaining power of coconut producers, in terms of commercial negotiation, varies according to the type of configuration that the transaction assumes. The theoretical framework is based on the Transaction Cost Economics (TCE) which, according to American economist Oliver E. Williamson (1985, 1991) relates the behavioral assumptions and attributes of the transaction to the choice of the governance structure that minimizes transaction costs. The hostage model approach was also used, where asset specificity is related to the construction of credible commitments between agents. On the other hand, the subsequent development of TCE, which describes the different types of hybrid forms of governance, were used to investigate the role of reputation, relational network, leadership, and formal governance as coordination mechanisms complementary to contracts. The methodology consists of an explanatory quantitative approach which utilizes the survey method of data collection. In this 2018 study, information was collected from 135 coconut transactions between the producer and the main buyer. The transactions were grouped into two categories: (a) “with commitment” and (b) “without commitment.” The information was analyzed by means of descriptive statistics with the use of hypothesis tests for the differences between the groups and, the use of a logistic regression, binary logit model, as it is the relationship of a binary categorical output variable with continuous predictive and other categorical variables. The results showed that the main factors explaining the adoption of hybrid governance structures are related to social aspects, such as the greater intensity of reputation built on recurring transactions. Results revealed Frequency as the main attribute of the transactions, since no significant asset specificities were found. Leadership was also identified as a relevant contractual complementarity, explained in this case by the authority exercised by the few buyers in the marketing channel.
Determinants of governance forms and contractual complementarities in the coconut producers negotiations in Alagoas State
Keywords: Agronegócio do coco; Formas híbridas de governança; Complementaridades contratuais; Coconut agribusiness; Hybrid forms of governance; Contractual complementarities; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO